RRP9 promotes prostate cancer metastasis and epithelial-mesenchymal transition through activation of the AKT/GSK3β/β-Catenin signaling pathway - Zijian Da; Yadan Du; Yawen Chen; Mingxu Da; Fenghai Zhou (Discover Oncology)
Abstract Ribosomal RNA Processing 9 (RRP9) is a gene associated with ribosomal function, and studies have demonstrated that its expression is aberrantly regulated in various tumor types, correlating with tumor progression. However, the specific role and underlying mechanism of RRP9 in prostate cancer (PCa) remain largely unexplored. In this study, bioinformatics analysis revealed that RRP9 is upregulated in PCa and is significantly associated with poor prognosis and lymph node metastasis. Further experimental data demonstrated that RRP9 knockdown notably inhibited the metastasis, invasion, and epithelial-mesenchymal transition (EMT) of PCa. Conversely, overexpression of RRP9 activated the AKT signaling pathway, resulting in the phosphorylation of GSK3β at Ser9, which in turn prevented β-catenin degradation and promoted cell metastasis, invasion, and EMT. Rescue experiments demonstrated that SC79 effectively reversed the inhibitory effects of RRP9 knockdown on PCa. These findings highlight the potential role of RRP9 in promoting the malignant biological behaviors of PCa, providing new insights and potential therapeutic strategies for the treatment of the disease.